Clinical implantation of 92 VACStents in the upper gastrointestinal tract of 50 patients—applicability and safety analysis of an innovative endoscopic concept - Lange, J.; Knievel, J.; Wichmann, D.; Kähler, G.; Wiedbrauck, F.; Hellmich, T.; Kandler, M.; Bernhardt, J.; Scholz, D.; Beyna, T.; Hausmann, J.; Wedi, E.; et al. (Frontiers in Surgery, 2023)
Endoscopic vacuum therapy (EVT) as novel treatment option for upper gastrointestinal wall defects is based on the principles of evacuation of secretions, removal of wound debris, and finally containment of defects improving the clinical outcome in the last decade. Covered stents however are hampered by a high rate of migration and missing functional drainage, whereas endoluminal EVT devices are limited by obstruction of the GI tract. The innovative design of the VACStent consists of a fully covered Nitinol-stent within a polyurethane-sponge cylinder, allowing EVT while stent passage is still open. The clinical experience of three different prospective study cohorts is analyzed regarding safe practicality (positioning, release of the stent), complete leak coverage and effective suction-treatment of esophageal leaks. Task of this study was to pool the data to get a broader base for analysis. In total, trans-nasal derivation of the catheter, suction and drainage of secretion via vacuum pump were performed without any adversity. In the pooled Study cohort of 92 VACStent applications, the mean stent indwelling time was 5.2 days (range 2-8 days) without any dislocation of the device. Removal of the VACStent was done without complication, in one case the sponge was lost but subsequently fully preserved. Minor local erosions and bleeding and one subsequent hemostasis were recorded unfrequently during withdrawal of the device (5.4 %, 5/92) but no perforation or pressure ulcer. Despite a high heterogeneity regarding primary disease and pretreatments a cure rate of 76 % (38/50 patients) could be achieved. In summary, insertion and release procedure was regarded as easy and simple with a low potential of dislocation. The VACStent was well tolerated by the patient while keeping the drainage function of the sponge achieving directly a wound closure by continuous suction and improving the healing process. The application of the VACStent offers a promising new option for improved clinical treatment in various indications of the upper gastrointestinal wall, which should be validated in larger clinical studies.